2014
DOI: 10.1159/000364826
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of Alcohol Dependence: A Review of Clinical Studies

Abstract: Background/Aims: Alcohol dependence is a common severe psychiatric disorder with a multifactorial etiology. Since the completion of the human genome project and with the increased availability of high-throughput genotyping, multiple genetic risk factors for substance-related disorders, including alcohol dependence, have been identified, but not all results could be replicated. Methods: We systematically review the clinical literature on genetic risk factors for alcohol dependence and alcohol-related phenotypes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0
9

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 176 publications
(202 reference statements)
0
16
0
9
Order By: Relevance
“…With the exception of an aldehyde dehydrogenase variant ( ALDH2*2 ) in East Asian populations, alleles of large effect have not been identified. 37 Although a number of common alleles have been identified through genome-wide association methods, these are of very small effect. 38 Thus, like other complex diseases such as diabetes 39 and traits such as height, 40 alcohol use is characterized by polygenic inheritance.…”
Section: Discussionmentioning
confidence: 99%
“…With the exception of an aldehyde dehydrogenase variant ( ALDH2*2 ) in East Asian populations, alleles of large effect have not been identified. 37 Although a number of common alleles have been identified through genome-wide association methods, these are of very small effect. 38 Thus, like other complex diseases such as diabetes 39 and traits such as height, 40 alcohol use is characterized by polygenic inheritance.…”
Section: Discussionmentioning
confidence: 99%
“…While the results of genetic association studies are thus far inconclusive with respect to actual disease risk (Samochowiec et al, 2014), studies of intermediate phenotypes have successfully demonstrated effects of genetic variability in the dopamine system on human motivational and cognitive processing (Meyer-Lindenberg and Weinberger, 2006; Yacubian et al, 2007; Richter et al, 2013, 2014; Wittmann et al, 2013). Most neurobiological investigations of addiction in humans and animals have highlighted the role of dysfunctional dopaminergic transmission in the ventral striatum/nucleus accumbens (NAcc) and reduced striatal D2 receptor availability (Kienast and Heinz, 2006; Everitt, 2014), but some authors have also pointed out the role of the hippocampus, which is critically involved in the formation of long-term memories (Robbins and Everitt, 2002; Robbins et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Several genes involved in alcohol metabolism, as well as genes involved in serotonergic, GABA-ergic, opioid, cannabinoid, dopaminergic and cholinergic transmission, were proposed to contribute to this heritability [5,6,8,26]. Recently published review of candidate gene-based studies, linkage studies and genome-wide association studies pointed out a limited role of individual genetic variants in the risk for alcohol dependence, although single risk variants within neurotransmitter signalling pathways may help to deepen the understanding of the underlying pathophysiology of alcohol dependence [21]. Serotonin (5-HT) has been shown to regulate alcohol consumption in both animals and humans and is considered to be involved in many aspects of alcohol consumption, abuse and dependence [10].…”
Section: Introductionmentioning
confidence: 99%